From Precariousness to Prudence: Eco-Cosmopolitanism as the Fabric for Weaving the Post-COVID World - Samanta, Nabanita (Kathmandu School of Law Review, 2020)
In a crucial juncture when the whole world has been shattered by the reign of a tiny virus invading the apparently invincible empire of human ‘civilization’, the plaguing pandemic has brought to the fore fundamentally interconnected nature of our collective existence and consequently our shared vulnerability. COVID-19 as essentially a zoonotic disease accentuates the anthropogenic hazards inflicted on the ecosystem resulting in spilling over of such pathogens from animals to humans. It also nudges us to reflect on our fundamentally interconnected existence which we have long remained oblivious about. The prevailing obliviousness seems to have emanated from willful ignorance or self-deceptive knowledge rooted in over-arching dictates of anthropocentrism; however on the structural front, the roots can be traced back to the capitalistic system perpetuating the ‘homo economicus’ aspirations so as to mark the unflinching triumph of the ‘Capitalocene’. While pushing and pulling ourselves to adapt to the ‘new normal’, it becomes an imperative to go beyond the myopic vision of restricting ourselves to short-term mitigation measures like border-closure or vaccination; instead time is ripe for taking a critical and broad-based stance on the structural roots of the current pandemic such that restructuration of post-COVID world helps shoving aside such calamitous disaster in days to come. It is in this regard, a radical take on ‘cosmopolitanism’ seems the need of the hour to fill the lacunae in the existing mode of perusing interconnectedness that operates only on the surface level in the name of ‘globalization’ and overlooks the fundamental rubric of ecological integrity. While shedding some light on the nexus that this pandemic shares with the evils of capitalistic enterprise and neoliberal culture of globalized consumerism, this paper, within its limited scope, will make an attempt to find an antidote to the current crisis through endorsing an ‘eco-cosmopolitan’ worldview wherein the rationalized ‘instrumentalization’ of environment and wild animals gets overridden by an eco-centric perspective on our fundamentally interconnected existence.